2009
DOI: 10.1177/0961203308093923
|View full text |Cite
|
Sign up to set email alerts
|

Association of programmed cell death 1 polymorphisms and systemic lupus erythematosus: a meta-analysis

Abstract: Programmed cell death 1 (PDCD1 or PD1) polymorphisms have been inconsistently reported to be associated with systemic lupus erythematosus (SLE). The aim of this study was to explore whether the PDCD1 polymorphisms confer a susceptibility to SLE and lupus nephritis (LN). We conducted a meta-analysis on the association of PDCD1 polymorphisms with SLE in overall and specific ethnic populations. A total of 15 separate comparisons were included in this meta-analysis consisting of nine Europeans, two Latin Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…Possible explanations for controversial results include clinical heterogeneity, ethnic differences, real genetic heterogeneity, and small sample sizes. Meta-analysis provides a useful means of analyzing inconsistent results because it increases sample size, and thus statistical power [18,26,27]. Accordingly, in the present study, because of the inconsistent results published on relationships between IL-6 polymorphisms and RA, we utilized meta-analysis to clarify associations.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for controversial results include clinical heterogeneity, ethnic differences, real genetic heterogeneity, and small sample sizes. Meta-analysis provides a useful means of analyzing inconsistent results because it increases sample size, and thus statistical power [18,26,27]. Accordingly, in the present study, because of the inconsistent results published on relationships between IL-6 polymorphisms and RA, we utilized meta-analysis to clarify associations.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome the limitations of individual studies and resolve inconsistencies, we performed this meta-analysis. [17][18][19] The aim of this meta-analysis was to systematically review the evidence on serum/plasma OPN levels in SLE patients compared to those in healthy controls and the correlation of OPN with disease activity, as well as determine whether OPN polymorphisms are associated with SLE susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…PDCD1 is expressed by activated T cells, B cells and myeloid cells and down-regulates B-and T-cell responses, making it a necessary negative regulator of self-reactivity. Many studies have shown the contribution of PDCD1 polymorphisms to SLE susceptibility in certain ethnic cohorts [52][53][54], and some studies have shown an association of certain PD gene alleles with lupus nephritis [55][56][57]. We propose that we could better stratify SLE patients by adding PD1 (CD279) to the cell-capture array.…”
Section: Other Markersmentioning
confidence: 99%